In-situ measurement of the stiffness of the foam layer in foam-adhesive bonded structures - Qin, S. (2010)
Foam-adhesive bonding is a common fabrication process in the aerospace, the automobile and the electronic industry. During service, the change with time in the behavior of components fabricated by this process is often caused by degradation of the foam layer within. As it is impractical, and at times impracticable, to dismantle the component for the purpose of testing and examining the foam layer, the need arises to develop methods of assessing the properties of the foam layer in situ. Many foam-adhesive bonded components comprise segments of strips bonded along their lengths to a rigid support. Additionally, these strips are secured with mechanical fasteners to prevent detachment from the support should the bonding fail. In this paper, a method is proposed which permits estimating the stiffness of the foam layer when the adherend (i.e., the strip) is subjected to point loads representing the forces exerted by the fasteners. The surface of the adherend is of mirror-like finish, as is found in the disk-drives industry. From the Moire fringe pattern generated with the use of the mirror-image method, the deflection of the adherend due to the point loads is deduced. Treating the foam layer as of the Winkler type, the magnitude of its stiffness is iterated using the theory of beams on elastic foundation.